Defining Visual Arts or Media to represent Sense of Religion Place in Tourism - Chonmaitre, Thirathep e (The Journal of International Buddhist Studies College, 2023)
During this COVID-19 era, the world is now living with COVID-19. This disease needs to be treated delicately. The widespread of this disease creates an impact throughout many different industries, especially with a social gathering. Social distancing has to be applied to stop the spreading of the disease. In solving the spreading problem, the online platform of any work or study activities has been adopted and applied in supporting social distancing and maintaining regular activities of work and study. Tourism is the one most important hit by this pandemic. In recovering the tourism industry, vaccination is the new hope to humankind. Stop spreading might be the new hope from vaccination while waiting for it. Moving into the online arena brings another hope of getting the tourism industry a new life. Sense of place is the key to connecting tourist and attraction place. Creating a sense of place through visual media can establish such a connection. Using visual art through an online platform might bring tourism to a new start. Using design thinking as a research methodology in searching for attraction place in religion and identifying the identity of religious place is the key to define the character of religious place. Therefore, matching the characteristic of religious places with visual art characteristics should bring a sense of religious place through the virtual environment later. 360 Photosphere or 360 Spherical panoramas, Color photographs, and Video tours are 3 types of visual art picked to represent religious places the best. At last, all three visual art or media can stimulate tourists in developing a connection between tourist and place. The development of realistic imagery from all 3 visual arts might shed some light on better visual media in religious places. Creating a sense of place environment for tourists to experience without traveling to the actual place while this pandemic is still going might be within reach.